ANALYSING FACTORS FOR COMMUNITY PARTICIPATION IN TOURISM DEVELOPMENT - Setiyorini, Heri Puspito Diyah; Andari, Rini; Masunah, Juju (Universitas Pendidikan Indonesia, 2019)
This study aims to understand the perceptions of local communities to participate in tourism development. The method used in the research is a quantitative approach. Questionnaires were distributed to local communities in major destinations in Bandung, West Java, Indonesia. There were 200 data set analyzed by factor analysis. The result showed that from 28 indicators of community participation, eight groups of factors formed. The groups are 1) place attachments; 2) perception of negative consequences; 3) Community Involvement; 4) Infrastructure Development; 5) Place Satisfaction; 6) Economic Benefit; 7) Government Support; 8) Community Collaboration. This result also shows that place attachment, perception of negative consequences, place satisfaction, and community collaboration have higher factor loading compares to other groups. The finding implies that in gaining community participation, these factors could be considered as the essence of communication message in raising public awareness and participation for tourism development.